EDUKASI MASYARAKAT TENTANG PENGOBATAN TRADISIONAL SANGKAL PUTUNG DALAM PENANGANAN PATAH TULANG DI JEMAAT GEREJA HERMON HOLLO HIM, SENTANI, KABUPATEN JAYAPURA - Rante, Indra Harianto; Labobar, Maryam Kathrien; Astawa, Gregorius Enrico; Hau Mahu, Grace Fitriani Primasari; Rumboirusi, Ricky Lazarus; Setyarini, Kaidah L.; Arwam, Fraymun (Jurnal Media Tropika, 2024)
Fractures are conditions where the continuity of bones, cartilage, or growth plates is lost due to trauma or non-trauma. Proper initial management can reduce the risk of disability caused by fractures. Delays in treatment can lead to disability. Several factors, such as community beliefs in traditional medicine, play a role. This activity aims to educate the community about the role of traditional “Sangkal Putung” treatment in fracture management. This seminar was held for the Hermon Hollo Him Church congregation in Sentani, Jayapura Regency. The methods used in this activity included lectures and interactive discussions. The seminar results showed that it successfully improved the congregation's understanding of the appropriate treatment options for fractures. It was concluded that this education is essential to help the community choose the optimal treatment methods for fracture cases.